The Cardioprotective Role of Flaxseed in the Prevention of Doxorubicin- and Trastuzumab-Mediated Cardiotoxicity in C57BL/6 Mice. Issue 9 (8th June 2020) - Asselin, Chantal Y; Lam, Amy; Cheung, David Y C; Eekhoudt, Cameron R; Zhu, Antonia; Mittal, Ishika; Mayba, Andrew; Solati, Zahra; Edel, Andrea; Austria, J Alejandro; Aukema, Harold M; Ravandi, Amir; et al.
ABSTRACT: Background: Although the combination of doxorubicin (DOX) and trastuzumab (TRZ) reduces the progression and recurrence of breast cancer, these anticancer drugs are associated with significant cardiotoxic side effects. Objective: We investigated whether prophylactic administration of flaxseed (FLX) and its bioactive components, α-linolenic acid (ALA) and secoisolariciresinol diglucoside (SDG), would be cardioprotective against DOX + TRZ–mediated cardiotoxicity in a chronic in vivo female murine model. Methods: Wild-type C57BL/6 female mice (10–12 wk old) received daily prophylactic treatment with one of the following diets: 1 ) regular control (RC) semi-purified diet; 2 ) 10% FLX diet; 3 ) 4.4% ALA diet; or 4 ) 0.44% SDG diet for a total of 6 wks. Within each arm, mice received 3 weekly injections of 0.9% saline or a combination of DOX [8 mg/(kg . wk)] and TRZ [3 mg/(kg . wk)] starting at the end of week 3. The main outcome was to evaluate the effects of FLX, ALA, and SDG on cardiovascular remodeling and markers of apoptosis, inflammation, and mitochondrial dysfunction. Significance between measurements was determined using a 4 (diet) × 2 (chemotherapy) × 2 (time) mixed factorial design with repeated measures. Results: In the RC + DOX + TRZ–treated mice at week 6 of the study, the left ventricular ejection fraction (LVEF) decreased by 50% compared with the baseline LVEF ( P < 0.05). However, the prophylactic administration of the FLX, ALA, or SDG diet was partially cardioprotective, with mice in these treatment groups showing an ∼68% increase in LVEF compared with the RC + DOX + TRZ–treated group at week 6 ( P < 0.05). Although markers of inflammation (nuclear transcription factor κB), apoptosis [poly (ADP-ribose) polymerase–1 and the ratio of BCL2-associated X protein to B-cell lymphoma–extra large], and mitochondrial dysfunction (BCL2-interacting protein 3) were significantly elevated by approximately 2-fold following treatment with RC + DOX + TRZ compared with treatment with RC + saline at week 6, prophylactic administration of FLX, ALA, or SDG partially downregulated these signaling pathways. Conclusion: In a chronic in vivo female C57BL/6 mouse model of DOX + TRZ–mediated cardiotoxicity, FLX, ALA, and SDG were partially cardioprotective.